PENERAPAN METODE KOOPERATIF MODEL GROUP INVESTIGATION UNTUK MENINGKATKAN PRESTASI BELAJAR IPS - Endang Sri Utami (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2015)
The purposes of the study were (1) to describe the application of group investigation model of cooperative method in learning IPS, (2) to describe an increase of learning IPS outcome through group investigation model of cooperative method, and (3) to describe the influence of group investigation model of cooperative method to students' motivation. The study was conducted at the sixth graders of the third state elementary school Pandanpancur, Deket - Lamongan in the academic year of 2013/2014, which was designed through action research approach (PTK) with two cycles. Each cycle was done through four stages: planning, implementation, observation and reflection. The results showed that the learning outcomes of students has increased from cycle I to cycle II, namely, the first cycle (61.28%), Cycle II (86.41%). The result gave the recommendation that the group investigation model of cooperative method can improve the students’ motivation and learning achievements at the sixth state elementary school of Pandanpancur, Deket - Lamongan.